Salary Satisfaction, Workload, and Job Satisfaction with Turnover Intention of Health Workers - Agus Setyono; Agusta Dian Ellina; Yenny Puspitasari; Andi Hayyun Abiddin (Sarana Ilmu Indonesia (Salnesia), 2025)
One option for community health services is the community health center (Puskesmas). Puskesmas can adaptably enhance health services by using the Regional Public Service Agency Financial Management Pattern (PPK-BLUD). However, it will affect health care by increasing the desire of health workers to leave if it is not backed by effective human resource management. The purpose of this study is to ascertain how health workers' intentions to leave their jobs relate to their workload, job satisfaction, and wage satisfaction. Using all 418 BLUD contract workers from 37 Puskesmas in Kediri Regency as the population, a cross-sectional design was employed. 204 participants who satisfied the inclusion criteria namely, having been employed as a contract employee at the Kediri Regency Health Center for more than six months were selected through the use of a straightforward random sample procedure. Data were gathered by a questionnaire in December 2023. Multiple linear regression was employed in the data analysis. The results showed that there was a significant relationship between workload (p-value = 0,001) and job satisfaction (p-value = 0,043) with turnover intention; however, salary satisfaction was not associated with turnover intention (p-value = 0,169). Long-term organizational success depends on effective planning as a method to enhance service quality. Puskesmas can hire BLUD contract workers based on employee payroll needs and strengths by implementing PPK-BLUD.